The Academic-Mental Health Nexus: Understanding the Correlation between Anxiety, Depression and Student Success at College Level (Journal of Social Sciences Review, 2024)
This study explores the relationship between mental health issues, such as anxiety, stress, and depression, and student success at the college level. A Correlational research design was utilized to carry out an investigation. A total of 7000 students from three private colleges of Multan, including Kips College Multan, City Science College Multan, and Punjab Group of Colleges Multan, served as the population. A sample size of 350 students was selected using a random sampling technique. A close-ended questionnaire was administered to analyze the impact of mental health on students' academic performance. Data was analyzed using descriptive and inferential statistics. Results of the study showed college students were greatly impacted by depression, stress, and anxiety. It was also perceived that students who were suffering from depression, stress, and anxiety had poor performance at the college level. It is recommended that students should be educated about the impact of depression, anxiety, and stress on their academic performance and alert them to the importance of seeing a mental health practitioner when their condition worsens.
Keywords: Mental Health; Students; Success; Anxiety; Stress; Depression